Marketing Strategy of Non-Franchise Convenience Stores in Silang, Cavite, Philippines - Soewignyo, Fanny (JBE (Journal of Business and Economics); Volume 9 No.2, 2010 JBE UNKLAB, 2010)
The principal purpose of the present study is to investigate a marketing strategy for non-franchise convenience stores in Silang, Cavite, Philippines based on the four Ps of the marketing mix: product, place, price and promotion. Convenience store in the study sells items such as candy, ice-cream, soft drinks, video media (CDs/DVDs), cigarettes and other tobacco products, newspapers and magazines, along with a selection of processed food and some groceries. Women dominate the bulk of daily customers who frequently visit the stores for groceries. Male customers came mostly to rent videos. All these customers came from large households and had been patronizing the store for the past two (2) years. The product diversification was weak, and although the product quality was considered satisfactory, customers find it compensating to have their items bought from the convenience stores near to them. However, there were not enough space within the stores, and their style of promoting the products and services were only by chance and word of mouth. Competitive environment holds overall business strategy.